Gene effects studies for earliness and seed yield in Indian mustard (Brassica juncea L. czern & coss.) - Singh, Kumar Kant; Singh, Rajendra; Singh, J.N.; Singh, Dhirender (Annals of Agricultural Research, 2014)
Gene effects were examined for earliness, days to 50 per cent flowering, number of primary branches, number of secondary branches, number of siliquae on main axis, number of seeds per siliqua, days to maturity, biological yield and seed yield from the six crosses selected from a 12 x 12 diallel mating design of [Brassica juncea (L.) Czern & Coss]. Genetic analysis showed that dominance effects were higher than additive for seed yield per plant in four crosses. Two crosses also showed additive x dominance effect indicated that non-additive gene action was predominant.